Bronchodilator reversibility testing in post-COVID-19 patients undergoing pulmonary rehabilitation. (June 2021) - Maniscalco, Mauro; Ambrosino, Pasquale; Fuschillo, Salvatore; Stufano, Silvia; Sanduzzi, Alessandro; Matera, Maria Gabriella; Cazzola, Mario
Abstract: Background: The usefulness of bronchodilators in coronavirus diseases 2019 (COVID-19) survivors is still uncertain, especially for patients with a concomitant obstructive lung disease. We aimed at verifying the level of bronchodilator reversibility in COVID-19 patients undergoing multidisciplinary pulmonary rehabilitation after the acute phase. Methods: We enrolled 105 consecutive patients referring to the Pulmonary Rehabilitation Unit of Istituti Clinici Scientifici Maugeri Spa SB, IRCCS of Telese Terme, Benevento, Italy after being discharged from the COVID-19 acute care ward and after recovering from acute COVID-19 pneumonia. All subjects performed a spirometry before and after inhalation of salbutamol 400 μg to determine the bronchodilation response within 48 h of admission to the unit. Results: All patients had suffered from a moderate to severe COVID-19, classified 3 or 4 according to the WHO classification, Seventeen patients had concomitant obstructive lung disease (14 suffering from COPD and 3 from asthma). FEV1 after salbutamol improved on average by 41.7 mL in the entire examined sample, by 29.4 mL in subjects without concomitant obstructive lung diseases, by 59.3 mL in COPD patients and by 320.0 mL in asthma patients. Mean FVC after salbutamol improved by 65.7 mL in the entire examined sample, by 52.5 mL in subjects without concomitant obstructive lung diseases, by 120.0 mL in COPD patients, and by 200.0 mL in asthma patients. Conclusions: This study suggests that a treatment with bronchodilators must always be taken into consideration in post-COVID-19 patients because it can induce a functional improvement that, even if small, can facilitate the breathing of these patients. Highlights: In post-COVID-19 patients, also bronchial obstruction can be present. The bronchial reversibility evaluation could be clinically important. Acute salbutamol induced a small functional improvement in post-COVID-19 patients. A treatment with bronchodilators must be taken into consideration in these patients.